Organization theory and design - Daft, Richard L. (Thomson/South-Western, 2007)
Richard Daft's best-selling text, Organization Theory and Design, integrates the most recent thinking about organizations, classic ideas and theories, and real world practice, in a way that is interesting and enjoyable for learners. This edition includes many updates including a new chapter on international issues and revisions of other chapters to include the most recent ideas and events. While organization studies and real world examples are insightful for understanding organizations and solve real-world problems, Daft also integrates numerous features that give learners opportunity to apply concepts and develop skills and insights